Dental caries and periodontal disease among U.S. pregnant women and nonpregnant women of reproductive age, National Health and Nutrition Examination Survey, 1999–2004. (6th May 2016) - Azofeifa, Alejandro; Yeung, Lorraine F.; Alverson, C. J.; Beltrán‐Aguilar, Eugenio
Abstract: Objectives: This study assessed and compared the prevalence and severity of dental caries and the prevalence of periodontal disease among pregnant and nonpregnant women of reproductive age (15–44 years) using data from the National Health and Nutrition Examination Survey, NHANES (1999–2004). Methods: Estimates were derived from a sample of 897 pregnant women and 3, 971 nonpregnant women. Chi‐square and two‐sample t ‐tests were used to assess differences between groups stratified by age, race/ethnicity, education, and poverty. Bonferroni method was applied to adjust for multiple comparisons. Results: In general, there were no statistically significant differences in the prevalence estimates of dental caries and periodontal disease between pregnant women and nonpregnant women. However, results showed significant differences when stratified by sociodemographic characteristics. For example, the prevalence of untreated dental caries among women aged 15–24 years was significantly higher in pregnant women than in nonpregnant women (41 percent versus 24 percent, P = 0.001). Regardless of their pregnancy status, racial/ethnic minorities or women with less education or lower family income had higher prevalence of untreated dental caries, severity of dental caries, and periodontal disease compared to the respective reference groups of non‐Hispanic whites or women with more education or higher family income. Conclusion: Results of this study show few clinical differences in dental caries and periodontal disease between pregnant and nonpregnant women but persistent disparities by sociodemographic characteristics. In order to reduce oral health disparities in the United States, it is important to improve access to oral health care particularly among vulnerable groups. Integrating oral health into the overall health care could benefit and improve women's oral health outcomes.